2014
DOI: 10.1002/cyto.a.22574
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the potential of standard flow cytometry by extracting fluorescence lifetimes from cytometric pulse shifts

Abstract: Fluorescence lifetime measurements provide information about the fluorescence relaxation, or intensity decay, of organic fluorophores, fluorescent proteins, and other inorganic molecules that fluoresce. The fluorescence lifetime is emerging in flow cytometry and is helpful in a variety of multiparametric, single cell measurements because it is not impacted by nonlinearity that can occur with fluorescence intensity measurements. Yet time-resolved cytometry systems rely on major hardware modifications making the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Even higher throughput could be achieved by measuring the phase shift of the fluorescence signal relative to the scatter signal. Both simulations and experimental data demonstrated that this parameter, called fluorescence pulse delay by the authors, reveals the fluorescence lifetime (10). Various FRET methods of common interest are listed in Table 1.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Even higher throughput could be achieved by measuring the phase shift of the fluorescence signal relative to the scatter signal. Both simulations and experimental data demonstrated that this parameter, called fluorescence pulse delay by the authors, reveals the fluorescence lifetime (10). Various FRET methods of common interest are listed in Table 1.…”
mentioning
confidence: 89%
“…An inventive approach to the latter has been implemented via converting a conventional inverted wide-field fluorescence microscope into a lifetime-measuring instrument by combining a microfluidics cell-handling system with time-correlated single photon counting. Both simulations and experimental data demonstrated that this parameter, called fluorescence pulse delay by the authors, reveals the fluorescence lifetime (10). Even higher throughput could be achieved by measuring the phase shift of the fluorescence signal relative to the scatter signal.…”
mentioning
confidence: 94%
“…We have demonstrated instruments that use digital laser modulation or pulsation, high speed data acquisition, and digital signal processing to provide fluorescence lifetime-based values for cell counting or sorting that operate at rates of thousands of cells per second [6][7][8][9]. These approaches for measuring fluorescence lifetimes with flow cytometers have involved both frequency-domain as well as time-domain methods.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated different versions of time-resolved flow cytometry [3,[7][8][9][10][11][12][13][14], and the main objective for augmenting flow cytometers to detect fluorescence lifetimes is to enhance cytometric data with a quantitative parameter that is independent of the measured fluorescence intensity [11,[15][16][17]. As a parameter, fluorescence lifetime can be used to discriminate among spectrally overlapping fluorescence signals as well as to validate the fluorescence intensity changes that arise from quenched fluorophores such as during Förster resonance energy transfer (FRET) events like those arising from changes in association state of tagged cytoplasmic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mass spectrometry combined with cytometry moves away from fluorescence‐based detection entirely by using antibodies tagged with rare earth metals, and in doing so easily achieves over 40 measured parameters per cell . Similarly, full spectral flow cytometry is pervasive, and ways in which fluorescence dynamics (i.e., fluorescence lifetimes) can be measured has gained acceptance in recent years . Again, not spatially dependent, these optical measurements add to the information content per‐cell in ways that alleviate issues with conventional systems.…”
mentioning
confidence: 99%